2015
DOI: 10.1080/21645515.2015.1011975
|View full text |Cite
|
Sign up to set email alerts
|

The compatibility of inactivated-Enterovirus 71 vaccination with Coxsackievirus A16 and Poliovirus immunizations in humans and animals

Abstract: Enterovirus 71 (EV71) is the key pathogen for Hand, Foot, and Mouth Disease (HFMD) and can result in severe neurological complications and death among young children. Three inactivated-EV71 vaccines have gone through phase III clinical trials and have demonstrated good safety and efficacy. These vaccines will benefit young children under the threat of severe HFMD. However, the potential immunization-related compatibility for different enterovirus vaccines remains unclear, making it hard to include the EV71 vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Although some other clinical studies have shown a weak cross-protective phenomenon in EV71 and CA16 infection [21,22], others have reported no cross neutralization or interference between EV71 and other enteroviruses, such as CA16 and polioviruses [23][24][25]. This nding is consistent with other ndings indicating that the EV71 vaccine is not protective against CA16, CA6, or other enterovirus infections [17].…”
Section: Discussionsupporting
confidence: 88%
“…Although some other clinical studies have shown a weak cross-protective phenomenon in EV71 and CA16 infection [21,22], others have reported no cross neutralization or interference between EV71 and other enteroviruses, such as CA16 and polioviruses [23][24][25]. This nding is consistent with other ndings indicating that the EV71 vaccine is not protective against CA16, CA6, or other enterovirus infections [17].…”
Section: Discussionsupporting
confidence: 88%
“…Clinical data collected by Kunming Children’s Hospital (the unique children's hospital in this city) elucidated that the number of EV-A71 positive patients in 2017 (1094 cases) and 2018 (822 cases) dropped sharply compared with 2015 (2672) and 2016 (3500). It was reported that EV-A71 circulates in 3–4 year cycles in Japan and Malaysia and CV-A16 circulates in a cyclical pattern of every 2–3 years in Singapore, England, and Wales [ 27 ]. However, the prevalence interval in most areas of China is mostly one year, and some provinces have been observed the characteristics of the periodic epidemic in 2–3 years.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we had established Standard Operating Procedures (SOPs) for the determination of enterovirus A71 and coxsackievirus A16 NtAbs 26 , 27 . EV-D68 NtAbs were detected in this study based on this previously reported method.…”
Section: Methodsmentioning
confidence: 99%